2001
DOI: 10.1046/j.1463-1326.2001.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granulocyte‐colony stimulating factor in the treatment of diabetic foot infection

Abstract: Although G-CSF improves neutrophil function as well as increasing the absolute numbers, this improvement is not associated with shortening of duration of antibiotic administration, duration of hospital stay or need for amputation in diabetic foot infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 26 publications
3
52
0
4
Order By: Relevance
“…DFI were more common in cases with duration of diabetes >10 years in our study which was also reported by Yonem A in his study that more the duration more the development of DFI. 13 Poor glycaemic controls with raised levels of HbA1c, long duration of hypertension were significant risk factors for development of DFI in our study and statistically significant association was found with these risk factors. Similar findings were reported by Lavery LA and Oyibo SO in their studies.…”
Section: Resultssupporting
confidence: 61%
“…DFI were more common in cases with duration of diabetes >10 years in our study which was also reported by Yonem A in his study that more the duration more the development of DFI. 13 Poor glycaemic controls with raised levels of HbA1c, long duration of hypertension were significant risk factors for development of DFI in our study and statistically significant association was found with these risk factors. Similar findings were reported by Lavery LA and Oyibo SO in their studies.…”
Section: Resultssupporting
confidence: 61%
“…In the second trial dealing with this subject, the beneficial effect of G-CSF could not be confirmed. G-CSF had no effect on the time until resolution of infection, nor on the duration of parenteral antibiotic administration or the duration of hospitalisation, despite an increased neutrophil function [6]. In contrast to these two studies, we quantified cellulitis and ulcer volume, ensured that all participants spent the same time period in the hospital, and insisted on bed-rest during the study period in order to guarantee consistent non-weight-bearing conditions for the ulcerated foot.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomised controlled clinical trials have investigated the therapeutic effects of G-CSF in infected diabetic foot ulceration, and yielded contradictory results [5,6]. The aim of our study was to re-evaluate the potential therapeutic effect of G-CSF in patients with infected foot ulcers.…”
mentioning
confidence: 99%
“…Secondly, and probably of greater clinical relevance, granulocyte-colony stimulating factor (G-CSF) has been used as adjuvant therapy in diabetic patients with foot infections. G-CSF induces terminal differentiation and release of PMN from the bone marrow and improves PMN function, particularly superoxide production [26][27][28]. In one trial [26], diabetic patients with lower limb infections who received G-CSF showed earlier microbial eradication from wound swabs, quicker resolution of cellulitis, and shorter duration of intravenous antibiotic administration and hospitalisation.…”
Section: Innate Immunitymentioning
confidence: 99%